Contribuição ao estudo de estratégias de modulação aplicadas a conversores multiníveis com diodos de grampeamento - Grigoletto, Felipe Bovolini (2009)
This dissertation deals with modulation techniques for multilevel diode clamped converters. The major challenge to be overcome by modulation strategies to these converters is the balance of the dc-link voltage capacitors, whilst minimizing the THD of output voltages. Among the modulation strategies reported in literature for this purpose are the carrier-based and space vector modulation techniques. Generally the space vetor methods select the nearest three vector to implement the desired output voltage vector. However, it is not always possible to remove the low frequency ripple in the dc-link voltage capacitors using this diagram vector. This work proposes a new space vector diagram that allows the elimination of the low frequency ripple in the dc-link voltage capacitors and guarantees the balance to the entire converter linear operation region, operating with any power factor load. Further constrains are derived based on the sign and magnitude of the output currents to determine the transition between the space vector diagram N3V and NS3V, making a hybrid modulation. As a result is possible to minimize the total harmonic distortion of the output voltages and to ensure the control of the averaged neutral point current. In order to make it possible to extend the results for converters with any number of levels, a carrier based modulation was proposed in this work where the modulation signals are chosen to ensure maximum use of the dc-link of the linear range of operation of converter, and eliminate low-frequency oscillation in the voltage capacitors. Moreover, it is proposed a space vector modulation strategy to back-to-back three level diode clamped converters, with the purpose to connect the wind power generation to the grid. This technique combines the utilization of the N3V and NS3V space vector diagrams for both converters connected to the same dc-link. Thus it is possible to establish a trade off between oscillation in the voltage capacitors and THD of output voltages. Experimental results and benchmarks are presented and demonstrate the good performance of the proposed methods.